Synergistic sonoelectrochemical removal of substituted phenols: Implications of ultrasonic parameters and physicochemical properties - Kim, K.; Cho, E.; Thokchom, B.; Cui, M.; Jang, M.; Khim, J. (Elsevier, 2015)
The effects of ultrasonic conditions and physicochemical properties on the synergistic degradation in synthetic solution were investigated. A wide range of ultrasound frequencies, including 35, 170, 300, 500 and 700 kHz, and ultrasonic power densities, including 11.3, 22.5 and 31.5 W/L were used. It was revealed that the physical effect of ultrasound plays a major role in synergistic mechanism and 35 kHz was found to be the most effective frequency due to its more vigorous physical effect induced by high implosive energy released from collapse of cavitation bubbles. The highest ultrasonic power density (31.5 W/L) showed the highest synergy index as it increases the number of cavitation bubbles and the energy released when they collapse. The synergy indexes of various substituted phenols under identical condition were investigated. These results were correlated with physicochemical properties, namely octanol water partition coefficient (Log K-ow), water solubility (S-w), Henry's law constant (K-H) and water diffusivity (D-w). Among these parameters, Log K-ow and D-w were found to have substantial effects on synergy indexes. (C) 2014 Elsevier B.V. All rights reserved.